Health insurance for university students in Bangladesh: A novel experiment. Issue 4 (1st October 2021) - Hamid, Syed Abdul; Khanam, Moriam; Azim, Md. Ragaul; Islam, Md. Sirajul
Abstract: Background and Aims: Bangladesh requires some pragmatic initiatives for using its immense potentiality to flourish health insurance. Introducing group health insurance for university students is a groundbreaking idea for stepping toward social health insurance in Bangladesh. This article examined the effect of the health insurance initiative for the university students introduced by the Institute of Health Economics, University of Dhaka, on attitude toward insurance and protecting financial risk against health care expenditure. Method: We used both management information system (MIS) and primary data obtained through mixed methods. We collected the quantitative data from a baseline survey on 310 students and a year‐end survey on 151 students. We used bivariate tools to analyze the data. Results: The results show that the mean score of attitude toward health insurance in the year‐end survey (4.04) was significantly higher than the baseline score (3.21). Results also show that a significantly higher percentage of the students reported insurance as "useful" in the year‐end survey (83.74%) than the baseline survey (40.40%). The results also reflectes that the scheme has a substantial impact on reducing the out‐of‐pocket spending for health care, especially for in‐patient care, and the anxiety regarding the financing of health care among the students. There is also an indication of sustainability and the feasibility of scaling up such a scheme across the country. Conclusions: Introducing such health insurance by all the universities may guide the nation toward large‐scale group health insurance and social health insurance.